Analisis Kepuasan Masyarakat Terhadap Kesigapan Kerja Dinas Pemadam Kebakaran dalam Penanggulangan Kebakaran di Kota Bengkulu - Tri Purwanti (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to determine public satisfaction with the response and alertness of the Fire Department in handling fires in Bengkulu City. The research method used in this study is a qualitative method. The results of the study indicate that, Service Procedure: The level of public satisfaction in the service sector is quite satisfied, because they give more satisfaction ratings than those who are dissatisfied. Service Discipline: The level of public satisfaction in the field of service officer discipline is less satisfied, because informants give more answers that are less satisfied. Responsibility: The level of public satisfaction with officers is satisfied, because there is only 1 informant who feels lacking, the rest give very satisfactory answers. Employee Competence: The level of public satisfaction in the field of employee competence is very satisfactory, because all informants give very satisfactory answers when interviewed. Suggestions in the Analysis of Public Satisfaction with the Alertness of the Fire Department in Handling Fires in Bengkulu City. Students who will conduct further research. It is advisable to find and read more other references. So that the results of further research are even better and gain new knowledge. The results of this study are expected to be used as reference material for researchers. It is expected that officers will be more careful in observing public responses. This is very important to anticipate future incidents. The limitation of this study lies in the informants, because they must be people who have reported the incident.